Why do people share memories online? An examination of the motives and characteristics of social media users. Issue 4 (21st April 2022) - Stone, Charles B.; Guan, Li; LaBarbera, Gabriella; Ceren, Melissa; Garcia, Brandon; Huie, Kelly; Stump, Carissa; Wang, Qi
ABSTRACT : Social media has become one of the most powerful and ubiquitous means by which individuals curate and share their life stories with the world at large. Not surprisingly then, researchers have started to examine the reasons why individuals post personal memories on social media and said individuals' characteristics . Across two studies, we extended this line of research by further testing the Purposes of Online Memory Sharing Scale (POMSS) and its subscales: self, social, therapeutic and directive. Additionally, we examined which of these motives led college students (Study 1) and adults of a community sample (Study 2) to post personal memories on social media and whether said motives were associated with the individuals' psychological characteristics. Overall, the results revealed that emerging adults and older adults posted personal experiences on social media primarily for social reasons. We also found that extraversion, disclosure and social media usage predicted each of the motives for posting personal experiences on social media. In addition, individuals who were more lonely and who had lower self-esteem were more likely to post personal experiences on social media for therapeutic reasons. We discuss these results in terms of their implications towards understanding the mnemonic consequences associated with social media use.